MULTIDISCIPLINARY STUDY OF ENVIRONMENTAL ETHICS PRESERVATION BASED ON LOCAL WISDOM THROUGH TRADITIONAL AGRICULTURE OF THE KAMPUNG NAGA COMMUNITY - Erni Mulyanie; Dede Rohmat; Iwan Setiawan; Bagja Waluya (GeoEco, 2026)
One of the indigenous communities in Indonesia that still practices a traditional agricultural system is the residents of Kampung Naga, Tasikmalaya. This community utilises the surrounding nature in accordance with the principle of conservation, aiming to maintain environmental sustainability for future generations. This study aims to examine environmental conservation activities and the role of local wisdom in the traditional agricultural system in Kampung Naga. A multidisciplinary approach is used to examine aspects of social geography, environmental ethics, and regional planning. The research method involves collecting primary data through observation, interviews, and documentation, complemented by a literature review. The results of the study indicate that the local wisdom of the Kampung Naga community plays a significant role in preserving the environment through a customary zoning system consisting of settlement areas, sacred forests, and agricultural land. These divisions regulate human–nature interactions that maintain ecosystem balance and sustainability. Traditional agricultural practices, supported by the Leuit (communal granary) and Goah (private granary) systems, ensure food availability and resilience in the face of crop failure or natural disturbances. This research also develops a conceptual model of environmental ethics based on local wisdom, integrating spatial management, ethical norms, and sustainable agriculture, which can be applied in other indigenous areas facing environmental challenges.